2018
DOI: 10.3390/pharmaceutics10040192
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Opioid Transport at the Blood-Brain Barrier by Altered ATP-Binding Cassette (ABC) Transporter Expression and Activity

Abstract: Opioids are highly effective analgesics that have a serious potential for adverse drug reactions and for development of addiction and tolerance. Since the use of opioids has escalated in recent years, it is increasingly important to understand biological mechanisms that can increase the probability of opioid-associated adverse events occurring in patient populations. This is emphasized by the current opioid epidemic in the United States where opioid analgesics are frequently abused and misused. It has been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 156 publications
(216 reference statements)
1
38
0
Order By: Relevance
“…Opioids are widely-used analgesics that bind with opioid and/or toll-like receptors (TLR) in the CNS ( Chaves et al, 2017 ; Yang et al, 2018 ). Transcellular solute and xenobiotic transport across the BBB is selectively controlled by the local influx and efflux transporters, including ATP-binding cassette (ABC), P-glycoprotein (P-gp, ABCB1), breast cancer resistance protein (ABCG2), multidrug resistance-associated proteins (ABCC) transporters, and solute carrier transporters ( Abbott et al, 2010 ; Chaves et al, 2017 ).…”
Section: Morphinementioning
confidence: 99%
“…Opioids are widely-used analgesics that bind with opioid and/or toll-like receptors (TLR) in the CNS ( Chaves et al, 2017 ; Yang et al, 2018 ). Transcellular solute and xenobiotic transport across the BBB is selectively controlled by the local influx and efflux transporters, including ATP-binding cassette (ABC), P-glycoprotein (P-gp, ABCB1), breast cancer resistance protein (ABCG2), multidrug resistance-associated proteins (ABCC) transporters, and solute carrier transporters ( Abbott et al, 2010 ; Chaves et al, 2017 ).…”
Section: Morphinementioning
confidence: 99%
“…These authors suggested pharmacodynamic interactions between opioids and cannabinoids. However, as opioid delivery to the brain is influenced by ATP-binding cassette transporters [ 49 51 ], a pharmacokinetic interaction should not be neglected.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…Neither codeine nor tramadol is Pgp substrates [ 51 , 57 ]. The polymorphic CYP2D6 regulates the O-demethylation of codeine and tramadol to more potent metabolites: morphine and O-desmethyl-tramadol, respectively.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…43 Morphine is able to diffuse through the EC membrane, and it also reaches the brain via active transport; however, it is subject to efflux via MRP and P-gp. [44][45][46][47][48][49] In contrast, codeine is not a substrate for MRP or P-gp and easily diffuses across the BBB. [48][49][50] Table 1 presents a summary of the permeability profiles for morphine, codeine and other currently marketed opioid receptor agonists and antagonists.…”
Section: Determinants Of Bbb Permeabilitymentioning
confidence: 99%
“… 44–49 In contrast, codeine is not a substrate for MRP or P-gp and easily diffuses across the BBB. 48–50 Table 1 presents a summary of the permeability profiles for morphine, codeine and other currently marketed opioid receptor agonists and antagonists.…”
Section: Introductionmentioning
confidence: 99%